2019
DOI: 10.1177/1744806919837429
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-induced aerobic glycolysis contributes to chemotherapy-induced painful peripheral neuropathy

Abstract: Chemotherapy-induced painful peripheral neuropathy (CIPN) is the most common toxicity associated with widely used chemotherapeutics. CIPN is the major cause of dose reduction or discontinuation of otherwise life-saving treatment. Unfortunately, CIPN can persist in cancer survivors, which adversely affects their quality of life. Moreover, available treatments are vastly inadequate, warranting a better understanding of the biochemical and metabolic mechanisms that occur in response to chemotherapeutics which wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 85 publications
(132 reference statements)
2
33
0
Order By: Relevance
“…Bortezomib and paclitaxel are known to reprogram the metabolism of sensory neurons in a manner consistent with aerobic glycolysis. 9,10 Crucially, targeted inhibition of the enzymes that maintain the aerobic glycolysis phenotype alleviate existing neuropathic pain, 10 suggesting that aerobic glycolysis is critical for the maintenance of CIPN. However, the mechanisms that sustain the expression of the enzymes that maintain aerobic glycolysis remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bortezomib and paclitaxel are known to reprogram the metabolism of sensory neurons in a manner consistent with aerobic glycolysis. 9,10 Crucially, targeted inhibition of the enzymes that maintain the aerobic glycolysis phenotype alleviate existing neuropathic pain, 10 suggesting that aerobic glycolysis is critical for the maintenance of CIPN. However, the mechanisms that sustain the expression of the enzymes that maintain aerobic glycolysis remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic glycolysis is characterized by enhanced glycolytic flux and reduced oxidative phosphorylation. Bortezomib treatment has been shown to limit mitochondrial oxidation of pyruvate, 10 which would deplete the metabolic intermediates that are essential for chromatin remodeling and altering the epigenetic landscape. 5559 Crucially, altered metabolic states are now recognized to produce epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested multifactorial pathways towards nerve fiber degeneration. Bortezomib induces aerobic glycolysis in sensory neurons, which may lead to the extrusion of metabolites sensitizing primary sensory afferents, finally causing pain [73]. One study in mice demonstrated bortezomib effects resulting in oxidative stress, mitochondrial dysfunction, cell apoptosis, and endoplasmatic reticulum stress [74].…”
Section: Mechanisms Of Action Of Immunomodulatory and Chemotherapeutimentioning
confidence: 99%
“…The effect of the CIPN-inducing proteasome inhibitor bortezomib on mitochondria in sensory neurons has also been investigated [56]. In a previous study bortezomib was shown to alter the metabolic phenotype of sensory neurons and increase the production of metabolites due to aerobic glycolysis, thus resulting in CIPN development.…”
Section: Oxidative Stressmentioning
confidence: 99%